Spatial variability of 2H and 18O composition of meteoric freshwater lakes in Scotland. Issue 3 (4th May 2019) - Hoogewerff, Jurian; Kemp, Helen F.; Leng, Melanie J.; Meier-Augenstein, Wolfram
ABSTRACT: Coastal regions, and in particular islands where precipitation from clouds formed out at sea occurs for the first time, are prime candidates for regions where 2 H and 18 O composition of precipitation will deviate significantly from the global mean geographic and physiographic trends of vapour-transport patterns. The results reported here are the outcome of a study that aimed to test this hypothesis by 'isotopographically' mapping the characteristic δ 2 H and δ 18 O signatures of Scottish freshwaters. The resulting isotope abundance landscapes or 'isoscapes' will underpin studies aiming to authenticate origin of Scottish produce but may also offer a baseline against which environmental changes could be assessed. Between April 2011 and May 2012 freshwater samples were collected from 127 different freshwater lochs and reservoirs across Scotland, and analysis results were compared to precipitation data provided by the British Geological Survey. Here we present the results of the 2 H and 18 O analyses of these water samples as well as the first detailed Scotland freshwater isoscapes with a grid resolution of about 5 × 5 km (0.05 degrees).